2016
DOI: 10.18632/oncotarget.11795
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between positron emission tomography and Cerenkov luminescence imagingin vivoandex vivousing 64Cu-labeled antibodies in a neuroblastoma mouse model

Abstract: Antibody-based therapies gain momentum in clinical therapy, thus the need for accurate imaging modalities with respect to target identification and therapy monitoring are of increasing relevance. Cerenkov luminescence imaging (CLI) are a novel method detecting charged particles emitted during radioactive decay with optical imaging. Here, we compare Position Emission Tomography (PET) with CLI in a multimodal imaging study aiming at the fast and efficient screening of monoclonal antibodies (mAb) designated for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…Our results are in accordance with other studies, which demonstrated a clear linear correlation between CLI radiance and PET using several radionuclides including 18-fluorine, 64-copper or 89-zirconium in vivo [911]. A close correlation between CLI and γ-counter-based biodistribution analysis has also been highlighted by several studies further validating this fast and cheap technique as a reliable alternative for high-throughput analysis [9, 11]. However, CLI imaging suffers from limitations.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are in accordance with other studies, which demonstrated a clear linear correlation between CLI radiance and PET using several radionuclides including 18-fluorine, 64-copper or 89-zirconium in vivo [911]. A close correlation between CLI and γ-counter-based biodistribution analysis has also been highlighted by several studies further validating this fast and cheap technique as a reliable alternative for high-throughput analysis [9, 11]. However, CLI imaging suffers from limitations.…”
Section: Discussionsupporting
confidence: 93%
“…We assume that the advantages of CLI are twofold: (i) fast imaging since the acquisition time for simultaneous PET-MRI imaging was about 40 min, whereas that of CLI was as low as 5 min and (ii) CLI signal remains proportional to the PET signal since both significantly correlated, consistent with previous data [2, 8]. Our results are in accordance with other studies, which demonstrated a clear linear correlation between CLI radiance and PET using several radionuclides including 18-fluorine, 64-copper or 89-zirconium in vivo [911]. A close correlation between CLI and γ-counter-based biodistribution analysis has also been highlighted by several studies further validating this fast and cheap technique as a reliable alternative for high-throughput analysis [9, 11].…”
Section: Discussionsupporting
confidence: 92%
“…This resulted in good tumor to background contrast from 2 days after tracer injection. Slow clearance of radioactivity from the blood is common for radiopharmaceuticals based on full-size monoclonal antibodies (24) and has in fact been observed previously with 64 Cu-labeled GD2-ch14.18 antibody in an animal model (25,26). The prolonged blood residence of the antibody conjugate will contribute to absorbed dose in blood-bearing organs such as the liver, spleen, heart, kidneys, and bone marrow.…”
Section: Discussionmentioning
confidence: 81%
“…3E8 is a humanized mAb against TAG-72 and has shown theranostic potential in colorectal cancer xenografts . For antibody fragment-based immunoPET imaging of TAG-72, PEGylated targeting vectors may serve as favorable surrogates for efficiently delivering the radionuclide to the tumor site while lowering kidney uptake. Delta-like 3 (DLL3), a Notch pathway ligand, has been identified as a marker for pulmonary neuroendocrine tumors (i.e., small cell lung cancer and large cell neuroendocrine carcinoma) and neuroendocrine PCas. As such, DLL3 may also serve as a tractable immunoPET imaging target. , Similar to the GPA33-targeted theranostic scenario, GD2-specific immunoPET imaging may help assess GD2 expression in patients with neuroblastomas. , Along with the clinical use of GD2-targeted antibody therapy and RIT, and future implementation of pRIT, GD2-targeted immunoPET imaging may guide precise anti-GD2 therapies and complement other imaging modalities to refine the management of neuroblastomas.…”
Section: Immunopet Imaging Of Cancersmentioning
confidence: 99%